PRAKTIK SOSIO-KULTURAL SEBAGAI BENTUK KEWARGAAN MASYARAKAT TAHUN 1950AN: MELIHAT KEMBALI HISTORIOGRAFI KEBANGSAAN DALAM BINGKAI NON-NEGARA - Suwignyo, Agus; Yuliantri, Rhoma Dwi Aria (Balai Pelestarian Kebudayaan Wilayah X, 2018)
Artikel ini mengkaji gagasan kewargaan sosial (social citizenship) dalam kehidupan sehari-hari masyarakat pada tahun 1950an. Sejauh mana proses menjadi Indonesia dalam dimensi sehari-hari tahun 1950an sebuah proses merakyat yang tidak elitis? Kajian dalam artikel ini memanfaatkan pemberitaan surat kabar sebagai sumber data. Dengan fokus-telaah pada agensi non-negara, artikel mengulas dimensi dan pola kewargaan yang dipraktikkan masyarakat melalui perkumpulan sosial, aktivitas kolektif masyarakat dan kegiatan-kegiatan budaya. Keterlibatan warga dalam berbagai saluran aktivitas menunjukkan tiga dimensi penting kewargaan sosial mereka. Pertama, wacana kewargaan yang cair dan terus mengalami negosiasi melalui perdebatan. Kedua, bentuk kewargaan sosial yang kebanyakan tersalurkan melalui aktivitas budaya sebagai objek material. Ketiga, ekspresi kewargaan sosial dalam aneka rupa perayaan terbuka sebagai cara komunitas-komunitas warga “menuntut” pengakuan publik atas keberadaan mereka. Ketiga dimensi menegaskan bahwa pembentukan kewargaan adalah proses sehari-hari masyarakat yang inklusif dan tidak selalu merupakan urusan negara.____________________________________________________________This article examines the practices of social citizenship in the daily life of the Indonesian people during the 1950s. In particular this article aims at answering the question: In how far was the process of being an Indonesian during the 1950s a people-based process not part of the state building project of the government? By using newspapers published in the 1950s as the sources of data, this article analyzes the dimensions of social citizenship that people perfomed through social organizations and communal and cultural activities. This article argues that the people’s participation in the many different channels of social and cultural activities during the 1950s showed three dimensions of social citizenship. First, it showedthat the people’s discourse of citizenship was ‘fluid’ and continuously adjusting to conform on-going negotiation and contestation. Second, communal and cultural activities were tangible forms of social citizenship through which people expressed their feeling as members of the Indonesian society. Third, carnivals and performances were a strategic medium for the people to acquire public recognition of their social existence.All the three dimensions suggested that the making of social citizenship during the 1950s was an inclusive process. They wereembedded in the daily life of the people and were relatively distant from the state’s project of nation building.